2011
DOI: 10.1063/1.3559266
|View full text |Cite
|
Sign up to set email alerts
|

Rietveld structure refinement, cation distribution and magnetic properties of Al3+ substituted NiFe2O4 nanoparticles

Abstract: Ferrite samples of Al3+ substituted NiFe2O4 nanoparticles were prepared by wet chemical co-precipitation method. The samples were obtained by annealing at relatively low temperature at 600 °C and characterized by x-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), vibrating sample magnetometry (VSM), and ac susceptibility. On applying the full pattern fitting of Rietveld method using FullProf program, exact coordinates of atoms, unit cell dimensions, atom ion oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 159 publications
(40 citation statements)
references
References 37 publications
4
36
0
Order By: Relevance
“…It was suggested that the observed reduction peaks, as well as their position could be related to the different Ni 2þ coordination in the spinel framework. Furthermore, they concluded that as the contribution of the b-peak in the total Ni species present in the spinel structure of NiAl 2 O 4 -CD was lower (27%) than that of NiAl 2 O 4 -CP (51%), the Ni 2þ ions occupying octahedral sites were more prone to reduction than the tetrahedral ones, as in the case of our 8NiAl-edf catalyst Thus, such results strongly support that the reforming efficiency is highly dependent on the type of interaction of the Ni active phase with the carrier [38,81,82].…”
Section: Role Of the Nickel Aluminate Spinel Phasessupporting
confidence: 79%
“…It was suggested that the observed reduction peaks, as well as their position could be related to the different Ni 2þ coordination in the spinel framework. Furthermore, they concluded that as the contribution of the b-peak in the total Ni species present in the spinel structure of NiAl 2 O 4 -CD was lower (27%) than that of NiAl 2 O 4 -CP (51%), the Ni 2þ ions occupying octahedral sites were more prone to reduction than the tetrahedral ones, as in the case of our 8NiAl-edf catalyst Thus, such results strongly support that the reforming efficiency is highly dependent on the type of interaction of the Ni active phase with the carrier [38,81,82].…”
Section: Role Of the Nickel Aluminate Spinel Phasessupporting
confidence: 79%
“…The small deviation between a th and a exp may be due to the presence of some ferrous ions Fe (II) ( ) on octahedral sites with larger radii than Fe (III) ( ) [23]. Using the values of "a", the radius of oxygen ion, , and r A in the following expression, the oxygen positional parameter 'u' can be calculated [24]:…”
Section: Structural Characteristicsmentioning
confidence: 99%
“…Fe 3+ and Mn 2+ ions randomly occupy A-site and B-site, non-magne tic Mg 2+ ions strongly prefer B-site and partially occupy A-site [35], Ni 2+ ions have strong preference to occupy B-site [36]. For the smaller concentr ation, In 3+ ions initially go to tetrahedral A-site and it prefer B-site for the higher concentratio n. Redistribution of the cations to less preferred sites has been considered only when required by calculated value of Fe occupancy of A and B sites.…”
Section: Cation Distributionmentioning
confidence: 99%